NTNU WriteFest 2020: A digital writing festival - Fagervik, Andreas; Langfeldt, Inga Buset; Lorange, Anne L.; Østerdal, Idun Knutsdatter (Septentrio Conference Series, 2021)
October is when the NTNU University Library usually offers physical writing events, assisting students with academic writing. For obvious reasons this was not possible in 2020, so we decided to create a digital event instead. We wanted to gather students who needed motivation and inspiration, and lecturers and librarians who could help, on the same platform at the same time. Our intention was to create a feeling of interdisciplinary community among the students as well as the employees, even though we weren’t in the same place physically. Not only did we want to reach out to all NTNU students across Norway, but also include the international students located abroad. The festival took place 12-16 October 2020 in The Virtual Library in Zoom (NTNU Universitetsbiblioteket, 2020), established during the lockdown in the spring of 2020. Events took place during the entire week, with the main event on Wednesday evening. The program focused on academic writing and related topics. We had lectures and courses with multiple internal and external contributors from NTNU, in addition to other services we offered during the week and evening. Parts of the event were also streamed to Facebook. There were a lot of firsts in the making of the festival. A digital writing festival for all students at NTNU had never been done before. The project group also consisted of members from different cities and departments and met only through online meetings. Working digitally presents new and other options when it comes to digital solutions and how to work together. In this presentation we will talk about our experiences, the do’s and don’ts we made along the way, and during the event. Things that work fine physically do not necessarily function well digitally.